Pengembangan E-Modul Berbasis Keseimbangan Otak Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Barisan dan Deret Geometri - Fatmawati, Vera; Adiastuty, Nuranita; Nurhayati, Nunu (Mathematic Education Departement, State Islamic University of Mataram, 2024)
This research aims to develop a brain balance-based module to improve students' mathematical creative thinking abilities on geometric sequences and series. The development of this e-module uses the Whole Brain Teaching (WBT) method, which is a brain balance method. The applications used in e-module development are Microsoft Office Word and Flip PDF Professional. This research is development research (Research and Development). The development model used in this research is the Plomp model which consists of three phases, namely the Preliminarity Phase, the Development or Prototype Phase, and the Assessment Phase. The instruments used in this research are validation sheets, practicality sheets and the N Gain Test instrument to see the effectiveness of the e-module. The result is that the validation test carried out by six media and material expert validators obtained an average score of 94.77% and was categorized as very valid. The results of the e-module practicality test carried out on teachers and students obtained an average score of 91.3% and were categorized as very good. Based on the N Gain test carried out in class e-module is categorized as medium.